Reassessment of Northern Kuwait Bay’s Dry-Stone Tombs: Insights into Architecture, Burial Practices, and Socio-Economic Dynamics - Steimer-Herbet, Tara; Hofstetter , Tobias; Achouche, Imane; Rutkowski, Łukasz; Varalli, Alessandra; Abegg, Claudine; al-Duweish, Sultan; Besse, Marie (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2025)
This paper examines the Late Neolithic, Chalcolithic, and Bronze Age dry-stone funerary monuments discovered along the northern coast of Kuwait Bay. The latter are studied in terms of funerary architecture, burial practices and socio-economic dynamics. Kuwait Bay appears to be situated at the crossroads between the influences of northern Arabian Neolithic tribes, as well as of Mesopotamian – and later – Dilmun trade networks. As such, its populations might have been part of a translocal economic scheme based on the trade of goods, either bound for, or originating from within these different realms. Accordingly, we aimed to assess the impact of these socio-economic and socio-cultural dynamics on a micro-regional scale, focusing on the imprint they might have left on Al-Subiyah’s communities and their architectural traditions, funerary behaviours and material cultures.